pyOpenMS-viz: Streamlining Mass Spectrometry Data Visualization with pandas - Sing, Justin Cyril; Charkow, Joshua; Walter, Axel; Gao, Mingxuan; Müller, Tom David; Bittremieux, Wout; Sachsenberg, Timo; Röst, Hannes Luc (Journal of proteome research, 2025)
Mass spectrometry data visualization is essential for a wide range of applications, such as validation of workflows and results, benchmarking new algorithms, and creating comprehensive quality control reports. Python offers a popular and powerful framework for analyzing and visualizing multidimensional data; however, generating commonly used mass spectrometry plots in Python can be cumbersome. Here we present pyOpenMS-viz, a versatile, unified framework for generating mass spectrometry plots. pyOpenMS-viz directly extends pandas DataFrame plotting for generating figures in a single line of code. This implementation enables easy integration across various Python-based mass spectrometry tools that already use pandas DataFrames to store MS data. pyOpenMS-viz is open-source under a BSD 3-Clause license and freely available at https://github.com/OpenMS/pyopenms_viz.